Enhanced single-cell RNA-seq workflow reveals coronary artery disease cellular cross-talk and candidate drug targets. (January 2022) - Ma, Wei Feng; Hodonsky, Chani J.; Turner, Adam W.; Wong, Doris; Song, Yipei; Mosquera, Jose Verdezoto; Ligay, Alexandra V.; Slenders, Lotte; Gancayco, Christina; Pan, Huize; Barrientos, Nelson B.; Mai, David; et al.
Abstract: Background and aims: The atherosclerotic plaque microenvironment is highly complex, and selective agents that modulate plaque stability are not yet available. We sought to develop a scRNA-seq analysis workflow to investigate this environment and uncover potential therapeutic approaches. We designed a user-friendly, reproducible workflow that will be applicable to other disease-specific scRNA-seq datasets. Methods: Here we incorporated automated cell labeling, pseudotemporal ordering, ligand-receptor evaluation, and drug-gene interaction analysis into a ready-to-deploy workflow. We applied this pipeline to further investigate a previously published human coronary single-cell dataset by Wirka et al. Notably, we developed an interactive web application to enable further exploration and analysis of this and other cardiovascular single-cell datasets. Results: We revealed distinct derivations of fibroblast-like cells from smooth muscle cells (SMCs), and showed the key changes in gene expression along their de-differentiation path. We highlighted several key ligand-receptor interactions within the atherosclerotic environment through functional expression profiling and revealed several avenues for future pharmacological development for precision medicine. Further, our interactive web application, PlaqView (www.plaqview.com ), allows lay scientists to explore this and other datasets and compare scRNA-seq tools without prior coding knowledge. Conclusions: This publicly available workflow and application will allow for more systematic and user-friendly analysis of scRNA datasets in other disease and developmental systems. Our analysis pipeline provides many hypothesis-generating tools to unravel the etiology of coronary artery disease. We also highlight potential mechanisms for several drugs in the atherosclerotic cellular environment. Future releases of PlaqView will feature more scRNA-seq and scATAC-seq atherosclerosis-related datasets to provide a critical resource for the field, and to promote data harmonization and biological interpretation. Graphical abstract: Image 1 Highlights: Automated cell annotation and pseudotemporal analyses reveal expression changes in de-differentiated smooth muscle cells (SMC). Ligand-receptor profiling reveals potential drug targets that modulate SMC and fibroblast signaling during atherosclerosis. Reproducible workflow allows for detailed evaluation of scRNA-seq datasets with minimal coding and eliminates potential bias. PlaqView web application allows for interactive analysis of scRNA-seq datasets and facilitates data sharing and reanalysis.